EFFECT OF HEALTH EDUCATION WITH THE PLAYING SNAKES AND LADDERS METHOD TO THE KNOWLEDGE OF ADOLESCENT ABOUT THE IMPACT OF CHILD MARRIAGE - Handayani, Sri; Monika, Rika; Pipit, Priska (Jurnal Kesehatan Samodra Ilmu (JKSI), 2020)
Background: Child marriage is a marriage carried out through civil, religious or customary law, and with or without official registration of records, where one or both partners are children under the age of 18 (BKKBN, 2017). Child marriage in Indonesia is ranked seventh in the world (UNICEF EAPR, 2017). Objective: To determine the effect of health education on adolescent knowledge about the impact of child marriage in SMP N 2 Paliyan Gunung Kidul Yogyakarta Methods: Pre-experimental research design with the One Group Pretest Posttest Technique. The population in this study were Paliyan SMP N 2 students totaling 106 people.The number of respondents was 33 people. The sampling technique used was purposive sampling. With bivariate data analysis using paired t test. Results: The results showed that the average knowledge before being given health care was 13.03, SD 2.11 and 95% CI with lower 12.28 and upper 13.78. After being given a penkes, the results obtained were an average of 14.45, SD 1.25 and 95% CI with lower 14.01 and upper 14.90. An increase in the average knowledge before and after being given health education is 1.42. Conclusions: There is an influence of health with the method of playing snakes and ladders to the knowledge of adolescents about the impact of child marriages in SMP N 2 Paliyan Gunungkidul Yogyakarta, proven by the p value of 0,000 <α = 0.05. Health education for adolescents using the snake and ladder play method on the effects of child marriages has an effect on increasing knowledge, with an increase in mean or average knowledge before and after health care is given is 1.42.